Microencapsulated repairing agent and intelligent self-repairing ultrahigh-strength ultrahigh-toughness cement-based structural material
By introducing multi-layer structural microcapsules and nanomaterials into concrete, the limitations of traditional concrete materials in terms of strength, toughness and durability are solved, and intelligent self-repair function and significant mechanical performance improvement are achieved, extending service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411500912.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Traditional concrete materials have limitations in strength, toughness and durability, and are prone to cracks and damage, especially in extreme environmental conditions, and the performance of existing intelligent self-repair materials is limited in their self-repairing effects at room temperature.
Using microencapsulation repair agents, the multi-layer structure microcapsules of the humidity-responsive outer layer, the pH-responsive intermediate layer and the temperature-responsive inner layer are introduced into the concrete, and combined with nanocarbon black, nanomontmorillonite and nanocellulose, the strength, toughness and durability of the concrete are significantly improved, and the intelligent self-healing function is equipped.
It significantly improves the self-repairing ability, mechanical properties and durability of concrete, enhances the scope of application and corrosion resistance of materials, extends service life, and reduces maintenance costs and resource consumption.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building materials, and specifically relates to a microencapsulated repair agent and an intelligent self-repairing ultra-high-strength and ultra-high-toughness cement-based structural material. Background Art
[0002] With the development of modern construction technology, the performance requirements for building materials are getting higher and higher. Traditional concrete materials have certain limitations in strength, toughness and durability, and are prone to cracks and damage, affecting the service life and safety of buildings. Especially under extreme environmental conditions, such as earthquakes, freeze-thaw cycles, chemical corrosion, etc., the performance of traditional concrete is even more insufficient.
[0003] In recent years, researchers have developed a series of high-strength, high-toughness and high-durability concrete materials by introducing high-performance materials and advanced preparation processes. However, these materials still face problems of cracks and damage during use. The generation of cracks will not only reduce the mechanical properties of concrete, but also lead to the penetration of water and other corrosive substances, further accelerating the deterioration of concrete.
[0004] In order to solve the above problems, the research on intelligent self-healing materials has gradually become a hot topic. Intelligent self-healing materials can automatically repair cracks and restore their original performance when the material is damaged by introducing a self-healing mechanism into the material. Self-healing mechanisms usually include microcapsules, shape memory alloys, nanomaterials, etc. These materials will release repair agents or repair cracks through physical and chemical reactions when they are stimulated by external factors (such as cracks). In the field of concrete, the application of self-healing technology is still in its infancy, but it has great potential. By introducing self-healing microcapsules into concrete, the durability and service life of concrete can be significantly improved, maintenance costs and resource consumption can be reduced, and it has important economic and social benefits.
[0005] In summary, the research on intelligent self-repairing high-strength and tough ultra-high performance concrete is not only of great significance in theory, but also shows broad prospects in practical applications. By rationally selecting and optimizing material components and preparation processes, concrete materials with excellent performance can be prepared to meet the needs of modern construction projects.
[0006] Chinese patent application CN115819034A: An ultra-high performance concrete material with high temperature self-repairing ability: This patent relates to an ultra-high performance concrete material that can self-repair under high temperature conditions, mainly composed of cement, silica fume, fly ash, quartz sand, steel fiber and high-efficiency water reducer. However, the self-repairing effect of this material at room temperature is limited, and the advantages of nanomaterials are not fully utilized. For example, at room temperature, the self-repair speed and effect of cracks are not ideal, which affects the overall performance of the material.
[0007] Chinese patent application CN103304206A ultra-high strength self-compacting concrete and its preparation method: This patent discloses an ultra-high strength self-compacting concrete, which is mainly composed of ordinary Portland cement, slag, silica fume, high-efficiency water reducer, fine aggregate, coarse aggregate and PVA fiber. Although the material has high strength and self-compacting properties, it lacks self-repairing function and cannot automatically repair cracks after they occur. In addition, the toughness and impact resistance of the material under high stress conditions need to be improved.
[0008] Chinese patent application CN202111442118 Self-sensing ultra-high performance concrete: This patent introduces a self-sensing ultra-high performance concrete that exhibits electromechanical effects under external loads by adding conductive additives to the concrete. Although the material has self-sensing functions, its self-healing ability is limited, and the introduction of conductive additives may affect other properties of concrete. For example, conductive additives may reduce the durability and corrosion resistance of concrete, limiting its application in practical engineering.
[0009] In summary, the existing technology has made some progress in improving the performance of concrete, but there are still many limitations. Summary of the invention
[0010] Purpose of the invention: In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a microencapsulated repair agent and an intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material. The present invention significantly improves the strength, toughness and durability of concrete by introducing self-repairing microcapsules with a specific structure, as well as materials such as nano carbon black, nano montmorillonite and nano cellulose, and has an intelligent self-repairing function.
[0011] Technical solution: In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0012] In a first aspect, the present invention provides a microencapsulated repair agent, which is mainly composed of a humidity-responsive outer layer, a pH-responsive middle layer, and a temperature-responsive inner layer, and the outer layer is modified with a silane coupling agent.
[0013] As a specific implementation scheme, the inner layer is mainly formed by a core material repair agent wrapped in a temperature-responsive shell material; the middle layer is mainly formed by a composite made of a pH-responsive material; and the outer layer is mainly formed by a polyurea structure made by cross-linking a humidity-responsive material.
[0014] As a preferred embodiment, the core material repair agent in the inner layer is selected from epoxy resin, and the shell material is selected from poly(N-isopropylacrylamide) (PNIPAM); the middle layer is mainly formed by a composite made of chitosan and polyacrylic acid; the outer layer is mainly formed by a polyurea structure made by cross-linking polyvinyl alcohol and phorone diisocyanate (IPDI); the silane coupling agent is selected from one of vinyl triethoxy silane, vinyl trimethoxy silane, and vinyl tri(β-methoxyethoxy) silane.
[0015] In a second aspect, the present invention provides a method for preparing the microencapsulated repair agent, comprising the following steps:
[0016] First, a temperature-responsive inner layer and a pH-responsive middle layer are prepared respectively, the inner layer is emulsified, and the middle layer is added for layer-by-layer self-assembly. Then, the obtained material is emulsified again, and the material for preparing the outer layer is added to form a three-layer structure through interfacial polymerization reaction. Finally, a silane coupling agent is modified on the surface of the material to obtain the microencapsulated repair agent.
[0017] As a specific embodiment, the preparation method of the microencapsulated repair agent comprises the following steps:
[0018] (1) Dissolve poly (N-isopropylacrylamide) PNIPAM in water to form a PNIPAM solution; disperse epoxy resin in an oil phase containing an emulsifier to form an oil phase; add the above PNIPAM solution to the oil phase, and PNIPAM undergoes polymerization reaction at the oil-water interface to form an inner layer-microcapsule structure in which PNIPAM encapsulates epoxy resin; the thermal response characteristics of PNIPAM cause it to undergo a volume phase change at a specific temperature, thereby encapsulating the repair agent to form a spherical or encapsulated material, and the solution and the emulsifier (polyvinyl alcohol) form a temperature-responsive inner layer through interfacial polymerization reaction.
[0019] (2) Dissolve chitosan and polyacrylic acid in acidic and alkaline solutions respectively, mix the two solutions to form a CS-PAA complex; emulsify the inner layer and add the CS-PAA complex solution to form an intermediate layer + inner layer structure through layer-by-layer self-assembly. CS is positively charged and PAA is negatively charged, and the two form a multilayer structure during alternating deposition. The deposition of each layer stabilizes the CS-PAA complex through electrostatic attraction and hydrogen bonding.
[0020] (3) PVA is dissolved in water to form a PVA solution; the above-mentioned middle layer + inner layer structure is emulsified again, and the PVA solution is added, and then isophorone diisocyanate IPDI is added to form a three-layer structure through an interfacial polymerization reaction; IPDI reacts with PVA at the interface to form a cross-linked polyurea structure, which wraps the multi-layer structure.
[0021] (4) A silane coupling agent is introduced into the surface of the three-layer structure to perform surface modification to improve dispersibility and stability. Finally, the prepared microcapsules are dried in a vacuum drying oven to remove the solvent to obtain the final product.
[0022] The repair mechanism of the above-mentioned microencapsulated repair agent is as follows:
[0023] Humidity sensing and response: When cracks form, the outer humidity response layer senses the humidity change at the crack and begins to dissolve or expand, exposing the middle layer. This process ensures that the microcapsules can begin to respond at the early stage of crack formation. pH sensing and response: When the middle pH response layer comes into contact with the alkaline environment in the concrete crack, it dissolves or expands, further exposing the inner layer. This process ensures that the repair agent is effectively released in the higher pH environment at the crack. The inner response layer releases the repair agent, which diffuses in the crack and reacts with the curing agent present in the original concrete to form a solid, filling the crack and restoring the strength and impermeability of the concrete.
[0024] In a third aspect, the present invention provides the use of the microencapsulated repair agent in the preparation of intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural materials.
[0025] In a fourth aspect, the present invention provides an intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material, comprising the following raw materials in parts by weight:
[0026] High-strength cement: 40-50 parts;
[0027] 16-23 parts of admixture;
[0028] Nano carbon black: 0.5-1 part;
[0029] Nano-montmorillonite: 1-2 parts;
[0030] Nanocellulose: 0.5-1 part;
[0031] The above-mentioned microencapsulated repairing agent: 2-5 parts;
[0032] Water reducing agent: 0.5~1.5 parts;
[0033] Curing agent: 1-2.5 parts;
[0034] Sand: 45-55 parts;
[0035] Water: 7-8 parts.
[0036] As a specific implementation scheme, the strength grade of the high-strength cement is PII525;
[0037] As a specific implementation scheme, the admixture is a mixture of fly ash and silica fume, with a mass ratio of 3: (3-5), wherein the silica content in the silica fume is ≥ 90%, and the specific surface area is 15-30 m 2 / g, the fly ash has a specific gravity of 1.77-2.43 g / cm 3 , fineness is not more than 12%, water requirement ratio is 100%~110%;
[0038] As a specific implementation scheme, the water reducer is a polycarboxylate water reducer with a water reduction rate of ≥30%;
[0039] As a specific embodiment, the curing agent is a polyamine curing agent, which is one of ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetramine (TETA) or a combination thereof;
[0040] The sand is quartz sand, with a maximum particle size of ≤1.25mm and a silicon dioxide content of ≥95%.
[0041] As a specific implementation scheme, the nano carbon black is mainly composed of carbon elements, usually containing a small amount of impurities such as oxygen and hydrogen, and has a density of 1.8-2.1 g / cm 3 , particle size is 10-50 nm, specific surface area is 200-1500 m 2 / g;
[0042] As a specific implementation scheme, the nano-montmorillonite is mainly composed of magnesium aluminum silicate and contains a small amount of calcium, sodium and water, with a density of 0.25-0.35 g / cm 3 The average particle size is between 10-50 nm, the chip thickness is less than 25 nm, and the specific surface area is 750 m 2 / g;
[0043] As a specific embodiment, the nanocellulose is mainly composed of natural cellulose, a polysaccharide formed by glucose units connected by β-1,4-glycosidic bonds, and is mainly a composition of cellulose nanocrystals (CNC) and cellulose nanofibers (CNF). The density is 1.5-1.6 g / cm 3 , particle size is 10-100 nm, specific surface area is 200-400 m 2 / g.
[0044] In a fifth aspect, the present invention provides a method for preparing the intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material, comprising the following steps:
[0045] (1) Material pretreatment: Disperse nano carbon black, nano montmorillonite and nano cellulose in part of water, perform ultrasonic dispersion, and form a nano suspension; mix the curing agent with the remaining water to form a curing agent suspension;
[0046] (2) Dry mixing: Mix high-strength cement, admixtures and sand and stir evenly to form a dry mixture;
[0047] (3) Wet mixing: gradually add the nano suspension and curing agent suspension into the dry mixture and stir to form a uniform slurry;
[0048] (4) Add the microencapsulated repair agent and continue stirring to ensure that the microcapsules are evenly distributed;
[0049] (5) Vacuum degassing: The mixed slurry is subjected to vacuum degassing treatment;
[0050] (6) Casting and molding: Pour the degassed slurry into a pre-prepared mold, remove residual bubbles, and then mold, demold, and maintain.
[0051] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0052] 1. Enhanced self-healing ability: mainly achieved through microencapsulated repair materials: (1) Multiple response mechanisms: through the dual sensing mechanisms of humidity response layer and pH response layer, the microcapsules can effectively respond at different stages of crack formation, improving the repair efficiency and accuracy. (2) Environmental adaptability: This multi-layer structure enables the microcapsules to adapt to different environmental conditions, such as humidity changes and pH changes, enhancing the application range and durability of the material. (3) Efficient repair: The design of the inner response layer ensures the efficient release and curing of the repair agent at the crack, improving the self-healing ability and service life of the concrete.
[0053] 2. Synergistic effect of multiple nanomaterials: The high electrical and thermal conductivity of nanocarbon black enables concrete to better disperse stress and heat when subjected to force or temperature changes, reducing the occurrence of cracks. At the same time, its high specific surface area and spherical particles can effectively fill the tiny pores in concrete, improving its density and compressive strength. Nanomontmorillonite has excellent adsorption and ion exchange capacity, can adsorb and fix organic matter, metal ions and gas molecules, enhance the durability and corrosion resistance of concrete, and can form a colloidal suspension in water, which can be evenly dispersed in concrete, improving the uniformity and poor stability of different nanomaterials. Nanocellulose has high strength and high modulus, which can significantly improve the tensile strength and toughness of concrete. The multilayer structure of the microencapsulated repair agent can respond to changes in humidity, pH value and temperature, and automatically release the repair agent when cracks are formed to fill the cracks. At the same time, the synergistic effect of nanocarbon black, nanomontmorillonite and nanocellulose can significantly improve the mechanical properties, durability and corrosion resistance of concrete. Nano carbon black fills the micropores, nano montmorillonite provides adsorption and ion exchange capabilities, and nano cellulose enhances mechanical properties.
[0054] 3. Excellent mechanical properties: The introduction of a variety of nanomaterials and their composite synergistic effect significantly improve the strength, toughness and impact resistance of concrete, making it perform better in various complex environments.
[0055] 4. Anti-permeability and corrosion resistance: The addition of nano-montmorillonite enhances the anti-permeability and corrosion resistance of concrete, reduces the penetration of water and other corrosive substances, and further extends the service life of concrete.
[0056] 5. Economic and environmental benefits: By improving the durability and self-repairing ability of concrete, maintenance costs and resource consumption are reduced, which has important economic and social benefits. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] The raw materials used in the following examples and comparative examples are as follows:
[0059] “Cement” is PII525 cement.
[0060] The “admixture” is a mixture of fly ash and silica fume in a ratio of 3:4. The specific gravity of fly ash is 2.1 g / cm 3 , fineness 10%, water requirement ratio 105%. The silica content of silica ash is 94%, and the specific surface area is 22 m 2 / g.
[0061] "High-performance water-reducing agent" is a polycarboxylic acid high-performance water-reducing agent with a water reduction rate of 35%.
[0062] The main component of "nano carbon black" is carbon, which is mainly composed of graphene layers and has a highly amorphous carbon structure. The morphology is spherical or nearly spherical particles. These particles aggregate through van der Waals forces to form larger aggregates, and the surface is porous and has a high degree of structural complexity. It is a by-product of incomplete combustion of petroleum-based heavy oil or creosote in a hot furnace or electric arc furnace at high temperature. Nano carbon black is mainly composed of carbon elements, usually containing a small amount of impurities such as oxygen and hydrogen, and has a density of 1.9 g / cm 3 , particle size is 20 nm, specific surface area is 1100 m 2 / g;
[0063] "Nano-montmorillonite" is composed of montmorillonite minerals, and its chemical composition is mainly magnesium aluminum silicate, and contains a small amount of calcium, sodium and water. After exfoliation, dispersion, purification, modification and ultra-fine grading, the average particle size is between 10-50 nanometers, and the thickness of the wafer is less than 25 nanometers. Montmorillonite is flaked into nano-scale flakes by mechanical means and adding dispersants, and uniform nanoparticles are obtained through ultra-fine grading technology. The main components of nano-montmorillonite are magnesium aluminum silicate, and contain a small amount of calcium, sodium and water. The density is 0.3 g / cm 3 The average particle size is between 25 nm, the chip thickness is 20 nm, and the specific surface area is 750 m 2 / g.
[0064] "Nanocellulose" is a mixture of cellulose nanocrystals (CNC) and cellulose nanofibers (CNF) in a ratio of 2:5. The former is a rod-shaped or needle-shaped structure, while the latter is a long fiber-shaped structure. Cellulose is dissociated and dispersed into nanocellulose through mechanical methods such as high-pressure homogenization and ultrasonic treatment. The density is 1.55 g / cm 3 , particle size is 75 nm, specific surface area is 300m 2 / g.
[0065] The "curing agent" is industrial grade ethylenediamine (EDA) with a purity of 99%.
[0066] “Sand” is quartz sand with continuous grading from 0 to 1.25 mm, the maximum particle size is ≤1.25 mm, and the silicon dioxide content is 98%.
[0067] The microencapsulated repair agent is prepared by the following method:
[0068] (1) Dissolve poly(N-isopropylacrylamide) PNIPAM in water and stir slowly for 30 minutes at room temperature until completely dissolved to obtain a 5.wt% PNIPAM solution; disperse 10g of epoxy resin in an oil phase (100ml) containing an emulsifier (2g) and stir slowly for 60 minutes at room temperature until completely dissolved to form an oil-in-water emulsion; mix the above PNIPAM solution with the oil-in-water emulsion in a volume ratio of 1:1 and stir slowly for 120 minutes at a temperature of 40 degrees. PNIPAM undergoes polymerization reaction at the oil-water interface to form an inner layer-microcapsule structure of PNIPAM encapsulating epoxy resin. The thermal response characteristics of PNIPAM cause it to undergo a volume phase change at a specific temperature, thereby encapsulating the repair agent to form a spherical or encapsulated material. The solution and the emulsifier (polyvinyl alcohol) form a temperature-responsive inner layer through interfacial polymerization reaction.
[0069] (2) Dissolve chitosan and polyacrylic acid in acetic acid and sodium hydroxide solutions respectively, stir at room temperature for 10 minutes to form 1.wt% solutions respectively, then mix the two solutions in a volume ratio of 1:1 and continue stirring for 30 minutes to form a CS-PAA complex; emulsify the inner layer and add the CS-PAA complex solution in a volume ratio of 1:1, stir at room temperature for 30 minutes, and form an intermediate layer + inner layer structure through layer-by-layer self-assembly. CS is positively charged and PAA is negatively charged, and the two form a multilayer structure during the alternating deposition process. The deposition of each layer stabilizes the CS-PAA complex through electrostatic attraction and hydrogen bonding.
[0070] (3) PVA was dissolved in water and stirred slowly at room temperature for 25 min until it was completely dissolved to form a 5 wt% PVA solution; the above-mentioned middle layer + inner layer structure was emulsified again, and the PVA solution was added at a volume ratio of 1:1, and then 2 g of isophorone diisocyanate IPDI was added, and the reaction was carried out at 50 degrees for 50 min to form a three-layer structure through interfacial polymerization reaction; IPDI reacted with PVA at the interface to form a cross-linked polyurea structure, which wrapped the multi-layer structure.
[0071] (4) 1.wt% silane coupling agent is introduced into the surface of the above three-layer structure for surface modification to improve dispersibility and stability. Finally, the prepared microcapsules are dried in a vacuum drying oven at 40 degrees for 24 hours to remove the solvent and obtain the final product. The preparation method of the low-yield intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material in each embodiment and comparative example specifically includes the following steps:
[0072] (1) Pretreatment of nanomaterials: disperse nano carbon black, nano montmorillonite and nano cellulose in part of deionized water respectively, and use an ultrasonic processor to perform ultrasonic dispersion for 30 minutes to ensure that the nanomaterials are evenly dispersed in water to form a nano suspension; Pretreatment of curing agent: mix the curing agent with the remaining water to ensure that it is evenly dispersed;
[0073] (2) Dry mixing: Add high-strength cement, admixtures and sand into the mixer in proportion and dry mix for 2-3 minutes to ensure that the components are evenly distributed;
[0074] (3) Wet mixing: gradually add the nano suspension and curing agent suspension obtained in (1) to the dry mixture obtained in (2), and continue stirring for 3-5 minutes until a uniform slurry is formed;
[0075] (4) Add the microencapsulated repair agent and continue stirring for 2-3 minutes to ensure that the microcapsules are evenly distributed in the concrete;
[0076] (5) Vacuum degassing: Place the slurry mixed in (4) in a vacuum degassing device for vacuum degassing for 5-10 minutes to remove bubbles in the concrete and improve its density and mechanical properties;
[0077] (6) Casting and molding: Pour the degassed slurry into a pre-prepared mold and use a vibrating table or manual vibration to further remove residual bubbles to ensure the density of the concrete. Molding is carried out at 20°C and the mold is removed after 24 hours. The slurry is placed in a water curing box and cured for 90 days under standard atmospheric pressure.
[0078] Table 1 Content of each component of ultra-high performance concrete in the examples and comparative examples
[0079]
[0080] The compressive strength and tensile strength tests of ultra-high performance concrete are carried out in accordance with GB / T 17671-1999 "ISO method for testing strength of cement mortar". The shrinkage is tested in accordance with T CECS 10107-2020 Technical requirements for ultra-high performance concrete.
[0081] Table 2 Mechanical properties and volume stability of ultra-high performance concrete in the examples and comparative examples
[0082]
[0083] From the results in Table 2 above, it can be seen that the embodiments have significant advantages in compressive strength, tensile strength and shrinkage by introducing materials such as self-repairing microcapsules, nano carbon black, nano montmorillonite and nano cellulose, reflecting the innovation and superiority of its materials and technologies. The material is more superior in bearing pressure and is suitable for high-strength applications. At the same time, the material performs well in resisting tensile forces and is suitable for high tensile strength applications. Most importantly, the material is more stable and less deformed during use, and is suitable for applications with high requirements for dimensional stability.
[0084] Table 3 Effect of the application of micro-nano materials on the mechanical properties and volume stability of concrete
[0085]
[0086] According to the results in Table 3 above, comparative examples 1-4 introduced multiple nanomaterials separately or without adding nanomaterials by setting up experiments, and compared with Example 2, it was found that the single small amount of these nanomaterials added had limited improvement on the performance of concrete, so in order to achieve better strength, toughness and durability, it is necessary to use these materials at the same time.
[0087] In addition, in order to evaluate the self-healing performance of the material, the crack self-healing test analysis method was adopted. 1. Prefabricated cracks: prefabricate cracks with a width of 0.3 mm on each concrete sample; 2. Curing conditions: place the sample in an environment of 20°C and 95% relative humidity for curing; 3. Observation period: observe the healing of the cracks every 7 days for 28 days. Use a crack width meter to measure and count the changes in crack width, and calculate the percentage of crack healing. The results are shown in the following table:
[0088] Table 4 Mechanical volume stability characterization of ultra-high performance concrete in Examples and Comparative Examples
[0089]
[0090] From the results in Table 4 above, it can be seen that the self-repairing effect of Comparative Example 5 is obviously inferior to that of the embodiment. The crack healing rate is low. This shows that without the introduction of self-repairing microcapsules and nanomaterials, the self-repairing ability and durability of concrete are significantly reduced.
[0091] The implementation modes of the present invention have been described in detail above in conjunction with specific embodiments, but the present invention is not limited to the above-mentioned implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A microencapsulated repair agent, characterized in that: The microencapsulated repair agent is mainly composed of a humidity-responsive outer layer, a pH-responsive middle layer and a temperature-responsive inner layer, and the outer layer is modified with a silane coupling agent.
2. The microencapsulated repair agent according to claim 1, characterized in that The inner layer is mainly formed by a core material repair agent wrapped by a temperature-responsive shell material; the middle layer is mainly formed by a composite made of a pH-responsive material; and the outer layer is mainly formed by a polyurea structure made by cross-linking a humidity-responsive material.
3. The microencapsulated repair agent according to claim 1, characterized in that: The core material repair agent in the inner layer is selected from epoxy resin, and the shell material is selected from poly (N-isopropyl acrylamide) (PNIPAM); the middle layer is mainly formed by a composite made of chitosan and polyacrylic acid; the outer layer is mainly formed by a polyurea structure made by cross-linking polyvinyl alcohol and phorone diisocyanate (IPDI); the silane coupling agent is selected from one of vinyl triethoxy silane, vinyl trimethoxy silane, and vinyl tri (β-methoxyethoxy) silane.
4. The method for preparing the microencapsulated repair agent according to any one of claims 1 to 3, characterized in that: The steps include: First, a temperature-responsive inner layer and a pH-responsive middle layer are prepared respectively, the inner layer is emulsified, and the middle layer is added for layer-by-layer self-assembly. Then, the obtained material is emulsified again, and the material for preparing the outer layer is added to form a three-layer structure through interfacial polymerization reaction. Finally, a silane coupling agent is modified on the surface of the material to obtain the microencapsulated repair agent.
5. The method for preparing the microencapsulated repair agent according to claim 4, characterized in that: The following steps are involved: (1) dissolving poly (N-isopropylacrylamide) PNIPAM in water to form a PNIPAM solution; The epoxy resin is dispersed in an oil phase containing an emulsifier to form an oil phase; the PNIPAM solution is added to the oil phase, and the PNIPAM undergoes a polymerization reaction at the oil-water interface to form an inner layer of the PNIPAM-encapsulated epoxy resin-microcapsule structure; (2) Dissolving chitosan and polyacrylic acid in an acidic solution and an alkaline solution, respectively, and mixing the two solutions to form a CS-PAA complex; emulsifying the inner layer, and adding the CS-PAA complex solution to form an intermediate layer + inner layer structure through a layer-by-layer self-assembly method. (3) PVA is dissolved in water to form a PVA solution; the intermediate layer + inner layer structure is emulsified again, and the PVA solution is added, and then isophorone diisocyanate IPDI is added to form a three-layer structure through an interfacial polymerization reaction; (4) Introducing a silane coupling agent onto the surface of the three-layer structure.
6. Use of the microencapsulated repair agent according to any one of claims 1 to 3 in the preparation of intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural materials.
7. An intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material, characterized in that: The invention comprises the following raw materials in parts by weight: High-strength cement: 40-50 parts; 16-23 parts of admixture; Nano carbon black: 0.5-1 part; Nano-montmorillonite: 1-2 parts; Nanocellulose: 0.5-1 part; The microencapsulated repair agent according to any one of claims 1 to 3: 2 to 5 parts; Water reducing agent: 0.5~1.5 parts; Curing agent: 1-2.5 parts; Sand: 45-55 parts; Water: 7-8 parts.
8. The intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material according to claim 7, characterized in that: The strength grade of the high-strength cement is PII525; the admixture is a mixture of fly ash and silica fume, with a mass ratio of 3:(3-5), wherein the silica content in the silica fume is ≥90%, and the specific surface area is 15-30 m 2 / g, the fly ash has a specific gravity of 1.77-2.43 g / cm³, a fineness of no more than 12%, and a water requirement ratio of 100-110%; the water reducer is a polycarboxylic acid water reducer with a water reduction rate of ≥30%; the curing agent is a polyamine curing agent, which is one of ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetramine (TETA) or a combination thereof; the sand is quartz sand with a maximum particle size of ≤1.25mm and a silicon dioxide content of ≥95%.
9. The intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material according to claim 7, characterized in that: The nano carbon black is mainly composed of carbon elements and has a density of 1.8-2.1 g / cm 3 , particle size is 10-50 nm, specific surface area is 200-1500 m 2 / g; The main component of the nano-montmorillonite is magnesium aluminum silicate, and the density is 0.25-0.35 g / cm 3 The average particle size is between 10-50 nm, the chip thickness is less than 25 nm, and the specific surface area is 750 m 2 / g; The nanocellulose is mainly composed of natural cellulose, a polysaccharide formed by glucose units connected by β-1,4-glycosidic bonds, with a density of 1.5-1.6 g / cm 3 , particle size is 10-100 nm, specific surface area is 200-400 m 2 / g.
10. The method for preparing the intelligent self-repairing ultra-high strength and ultra-high toughness cement-based structural material according to any one of claims 7 to 9, characterized in that: The following steps are involved: (1) Material pretreatment: Disperse nano carbon black, nano montmorillonite and nano cellulose in part of water, perform ultrasonic dispersion, and form a nano suspension; mix the curing agent with the remaining water to form a curing agent suspension; (2) Dry mixing: Mix high-strength cement, admixtures and sand and stir evenly to form a dry mixture; (3) Wet mixing: gradually add the nano suspension and curing agent suspension into the dry mixture and stir to form a uniform slurry; (4) Add the microencapsulated repair agent and continue stirring to ensure that the microcapsules are evenly distributed; (5) Vacuum degassing: The mixed slurry is subjected to vacuum degassing treatment; (6) Casting and molding: Pour the degassed slurry into a pre-prepared mold, remove residual bubbles, and then mold, demold, and maintain.
Citation Information
Patent Citations
Ultrahigh-strength self-compacting concrete and preparation method thereof
CN103304206A
Carbon nanomaterial compounded self-sensing ultra-high performance concrete and preparation method thereof
CN114276076A
Ultra-high performance concrete material with high-temperature self-repairing capability
CN115819034A
Water-tolerant light-resistant ozone-proof composition for protection of character image and cultural relics
CN104532669A
Stimulus-responsive self-repair anticorrosive coating material and preparation method
CN110105843A
Cited By
Pavement paving material and preparation method thereof
CN120157370A
Nanometer composite cement-based material and preparation method thereof
CN120736851A
Preparation method, product and application of chemical crosslinking hybrid shell phase change microcapsule
CN120961070A
High-durability airfield pavement quick repair composition, preparation method and quick repair method
CN121021092A
A high durability airport pavement quick repair composition, a preparation method and a quick repair method
CN121021092B